Graduate development trainee programs for students and graduates in certain companies - Bogdanova, Tatiana (2013)
Diploma thesis examines and assesses the process of recruitment, selection and hiring of students and graduates through development and training programs by the example of selected companies. The work consists of two parts - theoretical and practical one. The theoretical part describes types, content and basic properties of graduate recruitment development trainee programs for recent graduates and final year students. Practical part describes the programs and selection process for the programs by examples of international companies such as AB InBev, DHL and L'oreal. In final chapter of practical part there is a comparison of listed programs, author's advices and recommendations acquired during the selection process for development and training programs to listed companies. The work will be completed with author's conclusions.